Financial Knowledge and Saving Behaviors in Rural Areas of Thailand: A Descriptive Survey - Deenang, Exkarach; Sanubon, Poramet (International Conference on Multidisciplinary Research, 2020)
This paper aimed to identify: 1) the participant’s ability or disability to implement and utilize what they had learned, and 2) the participants’ financial behavioral changes and attitude changes towards managing money. Using the convenience sampling method, thirty attendees of the managing-money training project were selected to participate in Focus Group Discussions (FGDs). The interview questions were based on the OECD/INFE questionnaire of adult financial literacy. From the FGDs, it was found that most participants mainly relied on agricultural business, labor work, or private micro or small businesses. The FGDs also revealed that the participants had a general understanding of the basic financial knowledge, the implementation of income and expense tracking, budgeting as well as savings. Doing a family account was reported to be a new activity among the participants’ families. Children’s behaviors on expenses and irregular income streams were also found to be the major causes of their financial pressure. Developing the ability to balance income and expenses can be one solution for them to live without debt. However, some of the participants said that they did not have financial goals and would rather live for today than plan for tomorrow. Keywords: finance, saving-behaviors, money-management